The role of Chiefs as characters in Matsepe's novels : An appraisal - Segooa, Maite Stella (University of Limpopo, 2004)
In this research an attempt has been made to assess, evaluate and examine the role of chiefs as characters in Matsepe's novels. The need for this study was found to be necessary because no in-depth study of the role of chiefs in Matsepe's novels has as yet been undertaken. This study demonstrates how Matsepe portrays chiefs as characters in his novels, what their duties are and how they help in developing his themes.
Thesis (M.A. (African languages)) --University of Limpopo, 2004.
Keywords: Chiefs; Pedi (African people)-Social life and customs; Prose poems--South Africa